(untitled) (Torani Journal of Fisheries and Marine Science, 2018)
This research was conducted to know study of marine/fishery resource utilization at Ternate Manucipality, North Molucca when It was carried out at December, 2015 . Method of research was included qualitative descripted method. Research resulting showed that North Molucca has been contributed to export of fishery result which Ternate Manucipality had fisheries potential prospect for developing. Net working trading fresh and fickle fisheries in Ternate started fishermen to small and middle traider. If fresh fisheries was resulted, they would be brought to Manado to process and export later, while resulting of marine product was started from middle traider in Ternate to Tiongkok descent at Makassar and Surabaya that it were exported to the purpose of countries. Keywords: Fisheries resource, net working traiding, marine/fisheries fresh/fickle